PELATIHAN APPRECIATIVE INQUIRY UNTUK MENINGKATKAN EFIKASI DIRI WIRANIAGA DALAM MELAKUKAN TUGAS PENJUALAN - Sitepu, Neni Lala (Jurnal Psikologi, 2013)
Salesman performance and his effort is influenced by self efficacy. Appreciative inquiry is transformation in order to dig positive experiences that lead human future. The aim of this research is measuring the effect of appreciative inquiry training to improve self efficacy of salesman. Manipulation is conducted by experiental learning method. 36 participants was divided into two groups, experimental group (N=18) and control group (N=18). Characteristic of subject is salesman whose low self efficacy which selected by self efficacy scale. This research used untreated control group design with pretest-posttest. The result showed that mean of posttest (M=148.06) from experimental group is higher than pretest (93.94) and also in control group, posttest (M=88.11) and pretest (87.3). This means that both groups have a higher degree of self efficacy, with difference in experimental group is higher (M=54.12) than control group (0.81).Keywords: appreciative inquiry, self efficacy, salesman, untreated control group design with pretest-posttest